EFEKTIVITAS MODEL PROBLEM BASED LEARNING PADA MATERI PERTIDAKSAMAAN NILAI MUTLAK DI SMA - Fransklin yarso; Yulis Jamiah; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractEffectiveness of the Application of the Problem Based Learning Model in Inequalities of Absolute Value in class X of SMA 1 Sungai Raya. This study aims and determine the Effectiveness of the Application of the Problem Based Learning Model in Inequalities of Absolute Value. The method used was an experiment namely Pre-Experimental Design, in the form of The One case study. The research subjects were 36 students, namely class X IPA 4. The research location was in SMA Negeri 1 Sungai Raya. Data collection techniques use the direct observation, measurement, and indirect communication techniques. The data collection tool is in the form of an observation sheet. Data validity and reliability using Moment Product Correlation techniques and Alpha techniques. Data from questionnaires were analyzed using descriptive quantitative analysis. The implementation of teaching teachers is categorized as "very good", with a score of 3.61. Activities of students in the "active" category. Student learning outcomes do not reach the prescribed (classical) boundaries. Student responses provide a good response. In general, it was concluded that the application of the Problem Based Learning model in the Inequality of Absolute Value material in class X was declared less effective. It was suggested to the teacher that in using the Problem Based Learning model careful planning was needed so that the results are more accurate, using the Problem Based Learning model the problem given was the problem of the level of difficulty according to the level of thinking of students. Keywords: Effectiveness, Inequality of Absolute Value, Problem Based Learning